Uji Daya Hambat Solutio Belerang Terhadap Pertumbuhan Bakteri Propionibacterium acnes Secara In Vitro - Rindu Bunga Putri; Novita Carolia; Ety Apriliana (CV. Jasa Sukses Abadi, 2020)
Acne Vulgaris is an inflammation of the polysebaseal follicles indicated by the appearance of blackheads, papules, pustules, cysts and nodules, which often occur mainly in the chest (15%), face (99%), and back (60%). In Indonesia around 95-100% of men and 83-85% of women aged 16-17 years suffer from acne. One of the microorganisms that cause acne vulgaris is Propionibacterium acnes bacteria which is a normal flora on the skin. In treatment, acne vulgaris wide-spectrum antibiotics have been commonly used as a treatment for acne, as the time goes by, it has been found there are increasement of Propionibacterium acnes resistance to antibiotics like erythromycin, clindamycin, and tetracycline. Sulfur has been widely used in anti-acne products which have an antibacterial function and can inhibit the growth of Propionibacterium acne as a cause of acne. This study aims to test sulfur solutio with concentrations that are often used in anti-acne products, namely 2-10% in inhibiting P.acne bacteria. This type of research is an experimental laboratory with a well method. Solutio sulfur is divided by various concentrations of 10%, 8%, 6%, 4%, and 2%, with K (-) is distilled water, and K (+) is a clindamycin gel antibiotic. The data is based on the results of the measurement of the inhibition zone formed and tested with One Way Anova. The results of this study indicate the diameter of the inhibition zone formed sequentially, namely: 12.70 mm, 10.55 mm, 7.70 mm, 5.80 mm, 4.67 mm, positive control of 30,075 mm and negative concentration of 0 mm (p value = 0,001). There is an antibacterial effect of sulfur solutio with a concentration of 10%, 8%, 6%, 4% and 2% against Propionibacterium acnes bacteria.